Motif Politik Partai NasDem dalam Mengusung Romi Hariyanto–Sudirman pada Pilkada Provinsi Jambi Tahun 2024 dalam Perspektif Dimensi Idealisme - Adventa Theresia Pasaribu H; Subekti, Dimas; Qibtiyah, Mariatul (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study aims to analyze the political motives of the NasDem Party in endorsing Romi Hariyanto and Sudirman in the 2024 Jambi Provincial Election form the perspective of political idealism. The research focuses on two main aspect of idealistic incentives: the party’s political vision and the candidates’track records. Using a qualitative case study approach, data were collected through in-depth interviews, documentation, and analysis of official party sources. The findings reveal that NasDem consistently implements its idealistic values through the vision “Movement for Change”, locally embodied as Restorasi Jambi. The Party’s decision to nominate Romi-Sudirman is based on the alignment between the party’s ideological principles and the candidates’ integrity and administrative experience. Romi Hariyanto demonstrates strong leadership as a two-term Regent of Tanjung Jabung Timur, while Sudirman possess notable social engagement and moral leadership. These findings suggest that NasDem integrates political idealism with electoral pragmatism as a strategy to reinforce its value-based political identity. The study concludes that idealism can function as a strategic asset in contemporary political practice.